An Algorithm of Automated Identification of the Noun “думка” + Verb and Verb + Noun “думка” Metaphorical Model Meaning (Based on the Novel Музей покинутих секретів Written by Oksana Zabuzhko) - Karasov, Vitalii; Levchenko, Olena (My University, 2021)
The principles of automated identification of metaphoric combination of Noun “думка” + Verb and vice versa have been described in the thesis. The research has been carried out on the novel Музей покинутих секретів written by Oksana Zabuzhko and Grac v.10 corpus that served as the source of the research material. According to the search results in the text corpora, it was found that with the help of the models of two groups, both figurative and direct meaning can be realized. It should be noted that basically 71% of cases has figurative meaning and only rarely we come across a direct one. Such a feature of the considered metaphor’s models is due to the fact that the concept of “думка” is an abstract in itself. Due to this, the search field is significantly expanded and does not require preliminary screening of direct meanings of the lexeme “думка”. It should also be noted that the noun “думка” has such a semantic category t:ment r:abstr.
Keywords: Metaphor; automated identification of metaphor; semantically marked up corpus of texts